Budgetary financing of investments in the Republic of Uzbekistan - Khazratkulova, Lola (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article is devoted to the features of attracting and financing investments in the Republic of Uzbekistan, there shown a priorityof the investment sphere, since its development will make it possible to increase the efficiency of the use of raw materials, expand production of high-tech competitive products and ensure socio-economic development of the regions